Certificate of Completion and Compliance (CCC): Majlis Perbandaran Subang Jaya / Farisha Farhana Ismail - Farisha Farhana, Ismail (2017)
Majlis Perbandaran Subang Jaya (MPSJ) was established by the Local Government Act 1976 (Act 171) Section 4. Before declared MPSJ, it is known as Petaling District Council. In 1994, the State Government has decided to upgrade the Petaling District Council to the Subang Jaya Municipal Council. The purpose of this upgrade is to restructure the administrative organization to face the pressure of the physical, social, economic and environmental preservation.